Three women at the YWCA Cambrian Center - Unknown:::Creator::::::::::::
Photograph shows three young women standing at the doors to the YWCA Cambrian Center. The name and address of the center is on a sign above the doors and reads: "YWCA Cambrian Center 4343 Leigh Ave.